One stop or full stop? The continuing challenges for researchers despite the new streamlined NHS research governance process - France Emma F; Thompson Andrew GH (BMC, 2010)
Abstract Background Obtaining the necessary approvals and permission for clinical research requires successful negotiation of the ethical and R&D layers of the NHS. Differences in structure and governance frameworks feature between the constituent nations of the UK (England, Scotland, Wales and Northern Ireland), which adds complexity to cross-national studies. Difficulties in carrying out research in the NHS in the UK due to bureaucratic and time-consuming governance processes have led to the development of a new system of application and co-ordination from 2009. This paper illustrates how this new system fails to be consistent and streamlined and is unlikely to become so unless changes are made to the implementation and management of the governance processes. Methods We present a case study of the research governance process at the survey stage of an investigation into the use, preferences and need for information by people making choices or decisions about health care. The method involved home-based, face-to-face interviewing in a questionnaire survey in relation to decisions about lymphoma treatment, Down's syndrome screening in pregnancy, and caring for people with dementia. Results Our experience of the ethics stage was very positive, noting an efficient process of application and a speedy decision, both in relation to the initial application and to subsequent substantial amendments. By contrast, the R&D stages were very slow, most with unexplained delays, but some offering contradictory advice and exhibiting a lack of clear guidance and training for NHS staff. The R&D arrangements in Scotland were far quicker and more likely to be successful than in England. Overall, the delays were so severe that substantial parts of the research could not be delivered as planned within the funding timescale. Conclusions If high-quality research in the NHS, particularly in England, is to be delivered in a timely and cost-effective way, R&D processes for gaining research governance approval need improvement. Attention is needed in process implementation and management, particularly in relation to staff training, as well as clarity in guidance and communication within and between organisations.